Photo-Thermally Controllable Tumor Metabolic Modulation to Assist T Cell Activation for Boosting Immunotherapy - Ma J; Hua L; Zhu Y; Mao G; Fu C; Qin S (International Journal of Nanomedicine, 2024)
Jun Ma,1,* Lixin Hua,2,* Yinxing Zhu,3 Guangyao Mao,4 Chunsheng Fu,4 Shiyue Qin5 1General Surgery Department, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Third Hospital of Shanxi Medical University, Tongji Shanxi Hospital, Taiyuan, 030032, People’s Republic of China; 2Department of General Surgery, Affiliated Huishan Hospital of Xinglin College, Nantong University, Wuxi Huishan District People’s Hospital, Wuxi, People’s Republic of China; 3Department of Traditional Chinese Medicines, Taizhou Affiliated Hospital of Nanjing University of Chinese Medicine, Taizhou, 225300, People’s Republic of China; 4Institute of Clinical Medicine, the Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, 225300, People’s Republic of China; 5Department of Ophthalmology, the Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, 225300, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shiyue Qin, Email qinshiyue20230419@njmu.edu.cnBackground: Glycolysis is crucial for tumor cell proliferation, supporting their energy needs and influencing the tumor microenvironment (TME). On one hand, increased lactate levels produced by glycolysis acidifies the TME, inhibiting T cell activity. On the other hand, glycolysis promotes the expression of PD-L1 through various mechanisms, facilitating immune evasion. Therefore, controlled modulation of glycolysis in tumor cells to subsequently improve the immune tumor microenvironment holds significant implications for clinical cancer treatment and immune regulation.Methods: To reverse the immunosuppressive microenvironment caused by tumor glycolysis and reduce tumor immune escape, we developed a photo-thermal-controlled precision drug delivery platform to regulate tumor metabolism and aid in the activation of T cells, thereby enhancing immunotherapy. First, hollow mesoporous Prussian blue (HPB) was prepared, and the glycolysis inhibitor 3-bromopyruvate (3-BrPA) was encapsulated within HPB using the phase-change material 1-tetradecanol, resulting in B/T-H. This product was then modified with tumor cell membranes to obtain a photo-thermal controllable regulator (B/T-H@Membrane, B/T-HM).Results: Due to the excellent drug loading and photo-thermal properties of HPB, upon reaching the tumor, B/T-HM can rapidly heat under 808 nm irradiation, causing the 1-tetradecanol to transition to a liquid phase and release 3-BrPA, which effectively inhibits tumor glycolysis through the HK2 pathway, thereby reducing tumor cell proliferation, decreasing lactate production, and downregulating tumor PD-L1 expression. In synergy with photo-thermal and αPD-1, this photo-thermally controllable metabolic-immune therapy effectively activates T cells to eliminate tumor.Conclusion: In response to the changes in immune microenvironment caused by tumor metabolism, a photo-thermal precision-controlled drug delivery platform was successfully developed. This platform reshapes the tumor immunosuppressive microenvironment, providing a new approach for T cell-based tumor immunotherapy. It also opens new avenues for photo-thermal controllable metabolic-immune therapy.Keywords: photo-thermally controllable, glycolysis, PD-L1, T cell, metabolic-immune therapy